2014
DOI: 10.2134/agronj13.0579
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Bean Strip‐Intercropped with Maize: Evaluation of the CROPGRO Model

Abstract: Optimizing strip-intercropping systems requires a comprehensive modeling approach to study competition effects, especially for solar radiation, and to integrate numerous crops. Therefore, we studied the radiation availability and its effect on canopy and leaf level and finally on total dry matter and yield formation of bush bean (Phaseolus vulgaris L. var. nana) strip-intercropped with maize. Nine rows of bush bean were sown on two sowing dates between strips of six rows of maize (Zea mays L.). The CROPGRO mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…We assert that models would be useful tools to understand and predict the functioning of annual crop mixtures and to help designing these agroecosystems, as a complement to field experiments, keeping in mind that experiments are crucial to improve and refine simulation models whereas models are useful to guide experiments and test all possible plant-environment combinations (Craufurd et al 2013;Reynolds et al 2018;Rötter et al 2018). However, modeling of annual crop mixtures is still in its infancy, and most modeling studies focus on model evaluation (Gou et al 2017b) or the evaluation of sole crop models extended to crop mixtures, in particular for bi-specific mixture of annual crops (Corre-Hellou et al 2009;Knörzer et al 2010;Munz et al 2014). Use of modeling remains limited in part because models are not yet completely operational, indicating the need to increase understanding of the ecological processes that influence crop mixture functioning before simulating them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assert that models would be useful tools to understand and predict the functioning of annual crop mixtures and to help designing these agroecosystems, as a complement to field experiments, keeping in mind that experiments are crucial to improve and refine simulation models whereas models are useful to guide experiments and test all possible plant-environment combinations (Craufurd et al 2013;Reynolds et al 2018;Rötter et al 2018). However, modeling of annual crop mixtures is still in its infancy, and most modeling studies focus on model evaluation (Gou et al 2017b) or the evaluation of sole crop models extended to crop mixtures, in particular for bi-specific mixture of annual crops (Corre-Hellou et al 2009;Knörzer et al 2010;Munz et al 2014). Use of modeling remains limited in part because models are not yet completely operational, indicating the need to increase understanding of the ecological processes that influence crop mixture functioning before simulating them.…”
Section: Discussionmentioning
confidence: 99%
“…An initial strategy to simulate crop mixtures involved modifying how one crop senses its environment by altering environmental variables according to predictions of another sole crop model (i.e. successively running individual sole crop models, Monzon et al 2007) or external calculations (Knörzer et al 2010;Munz et al 2014). After calculating the impact of crop 1 on the environment, the modified environmental variables are used to simulate crop 2.…”
Section: Crop Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agronomic research on strip cropping with varying height plants has demonstrated the edge effects that increase yields of the taller species and often lead to a yield penalty for shorter crop plants (Jurik & Van, 2004). These studies were conducted in large‐scale farming in the United States (Ward et al., 2016; West & Griffith, 1992) and Argentina (Bravo & Silenzi, 2002; Verdelli et al., 2012), medium‐scale farming in Germany (Munz, Claupein et al., 2014), and small‐scale farming in China (Du et al., 2018; Liu et al., 2022; Munz, Claupein et al., 2014), as well as in Africa (Kermah et al., 2017; Rahman et al., 2021). Research on corn ( Zea mays L.), grain sorghum [ Sorghum bicolor (L.) Moench], and soybean [ Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%